Hubungan Perilaku Mom Shaming dengan Parenting Self-Efficacy Ibu - Zulri Ramadhan; Maya Oktaviani; Vania Zulfa (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2023)
ABSTRACT Parenting self-efficacy is parents' confidence in their competence in carrying out their role as parents, especially in parenting. A mother who has high self-confidence can help with the parenting process. This can be influenced by several parenting efficacy factors, one of which is social support. However, at this time, this is inversely proportional to the phenomenon that is currently rife, namely the phenomenon of mom shaming. Mom shaming is a behavior used as a pretext for criticism that embarrasses individuals regarding the role of mother and parenting style by positioning oneself as a more ideal individual in terms of parenting. Based on this, researchers conducted research to find out the relationship between mom-shaming behavior and parenting self-efficacy. The subjects of this study are mothers aged 20–35 years who have children aged 0–5 years and live in the South Jakarta area. The results of this study based on the Spearman rank correlation test obtained a value of 0.007<0.05, which means that there is a relationship between the variable